Rejeito de águas de dessalinizadores utilizados via hidroponia na irrigação do pimentão sob fertilização orgânica e mineral - Lima, Keivianne da Silva (2015)
Water is an essential factor in agriculture necessitating the new technologies to obtain, among these, the use of wastewater desalination plants is an alternative in this semiarid region. The salinity of the waste can be alleviated by the addition of organic matter to the culture system. In this context, this study aimed to evaluate the use of residual water desalination plants via hydroponics with organic manure on growth, nutrition and productivity of pepper plants. The research was conducted in pots with volume of 25 L, the Teaching Unit and Research of the Federal Institute of Education, Science and Technology of Ceará - IFCE in Limoeiro do Norte County, EC. The trial was conducted in open type hydroponics with the treatments distributed in a randomized block design in a factorial (5 x 4), for 5 different concentrations of saline water (0.5; 1.5; 3.0; 5.0; and 7.5 dS m-1) and 4 forms of fertilizer applications in the nutrient solution (biofertilizers concentrations: B1 = 50% of the recommendation by Guimarães (2013), B2 = 100% of the recommendation by Guimarães (2013) and B3 = 150% of the recommendation by Guimarães (2013)) and more (best mineral solution for hydroponics to the bell pepper crop), with 4 repetitions, totaling 80 experimental units, being used three plants per plot to obtain greater data reliability. Growth analysis on plant height, stem diameter and number of leaves were taken at 45, 60 and 75 days after transplanting - (DAT). The collection of plants and harvest the fruits were held at 75 DAT. The characteristics evaluated were: plant height, stem diameter, number of leaves, dry matter of the leaf, stem, root and total leaf nutrition, stem and root and fruit yield per plant. The results showed in the studied conditions, salinity and fertilization with biofertilizer and mineral did not influence significantly the growth in plant height, stem diameter and number of leaves at 75 DAT. Already the dry matter yield of leaf, stem, root and total were affected, with mass reduction in the most saline levels for dry mass of leaves and total. Productivity chili was influenced at 1% with up to 165g per plant in the application of biofertilizers 50% of the recommendation. The nutritional characteristics were influenced by the interaction salinity x fertilization, on the partition there were higher levels of N and K in the leaves with concentrations above recommended for culture and P, Ca, Mg and Na in the root system. The fertilization with 50% of the recommendation was adequate for growth and development of chili culture when used with moderate levels of salinity in irrigation water.